The Design and Impact of an Interprofessional Education Event Among Pharmacy and Nursing Students in Palliative Care—RnRx. Issue 4 (August 2020) - Houle, Sherilyn K. D.; Lillie, Elaine; Richard, Cynthia L.; Slivecka, Jenn; Miller, Andrea
Abstract : Nearly all reports of interprofessional education (IPE) in palliative care have excluded pharmacy students. This article describes an IPE event between pharmacy and nursing students and assesses its impact on IPE competencies. Second-year nursing students and third-year pharmacy students participated in an evening-long event, focused on a married couple who each require palliative care—one for end-of-life planning and one for chronic disease progression. The impact of the event was assessed using the Interprofessional Collaborative Competency Attainment Scale (ICCAS) and qualitative feedback. Two hundred nine (96.7%) completed the ICCAS, and 16 of the 20 statements of the ICCAS showed large positive effect sizes (Cohen d ≥ 0.8), with the remaining 4 showing moderate positive effect sizes (Cohen d ≥ 0.5). The greatest effect sizes were related to improved awareness of complementary skillsets and knowledge between the professions. Addressing team conflict and including the patient/family in decision-making showed the least improvement. While ongoing interactions are ideal for the development of skills related to conflict and team development, this article demonstrates that even a 1-time activity can have an impact on students' interprofessional care competence.